FAKTORFAKTOR YANG MEMENGARUHI TENSION TYPE HEADACHE EPISODIK PADA MAHASISWA KEDOKTERAN - Tony Hermawan,* Herlina Suryawati,* Maria Imakulata Widiastuti Samekto* (NEURONA, 2016)
INTRODUCTION TENSION TYPE HEADACHE TTH IS ONE OF THE PRIMARY HEADACHES WITH HIGH PREVALENCE RATES IN SOME STUDIES THE PREVALENCE OF TENSION TYPE HEADACHE RANGED BETWEEN 6078 IN MEDICAL SCHOOL ESPECIALLY DURING CLINICAL ROTATION STUDENTS ARE DEALING WITH VARIOUS KIND OF STRESS NEVERTHELESS TENSION TYPE HEADACHE RECEIVED LITTLE ATTENTION DUE TO THE ASSUMPTION THAT ITS NATURE IS MILD TO MODERATE